(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Combinatorial chemistry is one of the advanced method of synthesize the large number of molecules in short period of time. Synthesize the million number of same molecules are different molecules at a time. This method was fast and economic, then increase the competition between newer drugs in market. The present review describes that introduction about combinatorial chemistry, combinatorial library, techniques used in combinatorial chemistry and applications. Most commonly used combinatorial techniques are solid phase synthesis (in this technique resin beads, pins and chips are used as solid support, parallel synthesis, mixed combinatorial synthesis and solution phase synthesis. This technique was used in many areas such as pharmaceutical chemistry, biotechnology and agro chemistry. In combinatorial chemistry created large molecules can be detected efficiently